2017
DOI: 10.1039/c6ra27849c
|View full text |Cite
|
Sign up to set email alerts
|

Bi2O3 modification of HZSM-5 for methanol-to-propylene conversion: evidence of olefin-based cycle

Abstract: Bi2O3-modified HZSM-5 catalysts were prepared via a traditional wetness impregnation approach, and used for the methanol-to-propylene conversion reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In order to overcome this drawback, several procedures have been employed to reduce the limits of diffusion and improve the catalytic activity in the MTP reaction. Instances include optimizing the synthesis conditions (Jiao et al 2013), tuning the catalyst acid sites (Song et al 2017a;Li et al 2018a), reducing zeolite crystal size (Chen et al 2016b;Petushkov et al 2011), and modification with different proper metallic and non-metallic additives such as magnesium, nickel, iron, iridium, chromium, cerium, phosphorus and the like by using incorporation, impregnation, and ion-exchange procedures (Bai et al 2016;Chen et al 2015;Gorzin and Yaripour 2019;Valle et al 2005;Yarulina et al 2016;Hadi et al 2016;Yuan et al 2019;Zhang et al 2017). Among these methods, the introduction of a promoter is a high-performance route of altering the acidity in zeolites (density and strength), hence enhancing the catalytic efficiency of the H-ZSM-5 catalyst in the MTP process and stimulating higher selectivities to propylene (Bai et al 2016;Valle et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this drawback, several procedures have been employed to reduce the limits of diffusion and improve the catalytic activity in the MTP reaction. Instances include optimizing the synthesis conditions (Jiao et al 2013), tuning the catalyst acid sites (Song et al 2017a;Li et al 2018a), reducing zeolite crystal size (Chen et al 2016b;Petushkov et al 2011), and modification with different proper metallic and non-metallic additives such as magnesium, nickel, iron, iridium, chromium, cerium, phosphorus and the like by using incorporation, impregnation, and ion-exchange procedures (Bai et al 2016;Chen et al 2015;Gorzin and Yaripour 2019;Valle et al 2005;Yarulina et al 2016;Hadi et al 2016;Yuan et al 2019;Zhang et al 2017). Among these methods, the introduction of a promoter is a high-performance route of altering the acidity in zeolites (density and strength), hence enhancing the catalytic efficiency of the H-ZSM-5 catalyst in the MTP process and stimulating higher selectivities to propylene (Bai et al 2016;Valle et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the olefin selectivity was improved over Mg- and Zn-doped monolith catalysts. Various methods have been reported in the literature to improve the catalytic activity and performance of HZSM-5, comprising generation of mesoporosity in microporous HZSM-5 (to overcome diffusion limitation and postpone the catalyst deactivation via desilication) and alteration in zeolite acidity (to increase propylene selectivity via doping with some metals). Our former study showed that the synergetic modification by controlled desilication and Mn impregnation over high-silica HZSM-5 catalyst plays a positive role in propylene selectivity and catalyst activity …”
Section: Introductionmentioning
confidence: 99%
“…As one of the most important reactions in C1 chemistry, the methanol to propylene (MTP) process has the potential to play an increasing role in global chemicals manufacture. It has gained much attention these years, because of producing propylene with high selectivity via methanol from natural gas, coal, shale gas and biomass [6][7][8][9][10]. In order to understand the MTP process (prolonging the lifetime of catalyst, raising the catalyst activity, getting the best distribution of products), various studies of the MTP reaction have gained considerable attention of many researchers in the past decades [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%